O discurso de resistência em recortes de Sobrevivendo no inferno (2018) do Racionais MC’S - Silva, Daniel da Rocha (2022)
In this study, we mainly purpose to analyse the process of sense production by means of three discursive sequences: “Capítulo 4, versículo 3”, “Diário de um detento” and “Perifiria é periferia (em qualquer lugar)”, from the book Sobrevivendo no inferno (2018), published by Editora Companhia das Letras. This book is a printed version of the homonymous album released in 1997 by the rap group Racionais MC’s in the midst of an era marked by police violence against the peripheries of São Paulo. The work chosen to present linguistics marks that allow the discourse analyst to interpret the implicit senses, the flaws in the discourse of resistence, as well as the displacements and continuity of it. By what means does rap music “denounce” this reality? It is known that rap music influences its listeners to keep a constant watch over the actions of the State, since they represent subjects of discourse that resist to the absence of public policies. Seen in these terms, by means of Pechetian discourse analysis, we aim to understand how the corpus approaches the discourse of resistance from the 1990’s conditions of production, a time strongly remarked by massacres that raise questions regarding their executors even today; consequently, our specific aims are: to discover the 1990’s conditions of production; to identify how such a subject of discourse is ideologically influenced within its discursive formation and to verify how the subject of discourse resists the dominant ideology of a capitalist social formation. Thus, it is justified for being an influential musical group that permeates the various socioeconomis strata of society that doesn’t restrict itself to the periphery, fact that marked the national rap music and made it reach a great notability. Therefore, rap music is the periphery’s voice among the medias, it enters in diverse social spaces and reaches diverse social agents. Since our theoretical guide is the Discourse Analysis which doesn’t have a fixed and unique methodology, there are movements of interpretation by the analyst according to his contact with the corpus, the categories of analysis and as the research pregresses instead. For this purpose, we base our work on the theoretical contributions of Discourse Analysis’ main author: Michel Pêcheux (1995; 1997; 2020); besides Orlandi (2000; 2007; 2012), Maldidier (2017) and others. Thus, we consider some concepts presented by Pêcheux, such as: ideology, discursive formation, memory, event, interdiscourse, sense, conditions of production and subject. We assess that periphery’s subject of discourse is cleaved by a discourse of resistance and this is manifested in Racionais